UJI EFEK PENYEMBUHAN LUKA SAYAT EKSTRAK ETANOL DAUN KECOMBRANG (Etlingera elatior) DALAM BENTUK SEDIAAN GEL TERHADAP KELINCI (Oryctolagus cuniculus) - Gemy Nastity Handayany; Mukhriani Mukhriani; Rezkiyana Mulya Halim (Universitas Islam Negeri Alauddin Makassar, 2015)
Has done research on Wound Healing Cut Effects of Ethanol Extract Leaf kecombrang (Etlingera elatior) In Categories Gel Against Rabbit (Oryctolagus cuniculus). The aim was to evaluate the efficacy and the optimum concentration of the extract healing cuts kecombrang (Etlingera elatior) in a gel dosage form. Variants concentration used was 5%, 7%, and 9%. The method used is the sample extraction by maceration and wound gel is made in 3 concentrations of 5%, 7%, and 9%. In addition it is also used as a negative control base gel and gel Bioplacenton® as a positive control, then back skin of rabbits (Oryctolagus cuniculus) were wounded using a scalpel.Results of statistical analysis using the method Annova completely randomized design showed that the leaf gel preparations kecombrang (Etlingera elatior) may decrease and cuts heal in rabbits with a concentration of 9% which shows the effect of healing the most effective cuts.